2004
DOI: 10.1161/01.str.0000125863.93921.3f
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Outcome of Ischemic Stroke in Patients Pretreated with Statins

Abstract: Background and Purpose-Statins may be beneficial for patients with acute ischemic stroke. We tested the hypothesis that patients pretreated with statins at the onset of stroke have less severe neurological effects and a better outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
131
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(147 citation statements)
references
References 32 publications
15
131
1
Order By: Relevance
“…However, this decreased MMP-9 level did not result in improved clinical outcome [61] . While atorvastatin has previously been shown to correlate with reduced incidence [62] and improved neurological outcomes in cerebrovascular disease, these results highlight the potential link between statins and serum MMP inhibition in neurologic injury [63][64][65][66] . Sinn et al demonstrated that valproic acid (VPA) treatment in rats with ICH decreased levels of MMP-9 mRNA.…”
Section: Chang Jj Et Al Mmp Regulation In Intracerebral Hemorrhagementioning
confidence: 70%
“…However, this decreased MMP-9 level did not result in improved clinical outcome [61] . While atorvastatin has previously been shown to correlate with reduced incidence [62] and improved neurological outcomes in cerebrovascular disease, these results highlight the potential link between statins and serum MMP inhibition in neurologic injury [63][64][65][66] . Sinn et al demonstrated that valproic acid (VPA) treatment in rats with ICH decreased levels of MMP-9 mRNA.…”
Section: Chang Jj Et Al Mmp Regulation In Intracerebral Hemorrhagementioning
confidence: 70%
“…decreasing incidence of cortical infarcts). Indeed, statin (HMG-coA reductase inhibitor) and fibrates decrease the CRP levels, and favorable outcome among ischemic stroke patients pretreated with statin was recently reported [36,37]. Further investigations are warranted to elucidate the effects of these agents as a potential stroke phenotype modifier.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the effect of statin treatment in stroke prevention, it has also been shown that statins (HMG-CoA reductase inhibitors) have other beneficial effects and these may be independent of the subject's basal lipid levels (47,86). In fact, recent studies suggest a neuroprotective power in the acute phase of stroke.…”
Section: Other Treatmentsmentioning
confidence: 99%